2021
DOI: 10.1007/s43762-021-00002-1
|View full text |Cite
|
Sign up to set email alerts
|

The projected impacts of smart decline on urban runoff contamination levels

Abstract: There has been mounting interest about how the repurposing of vacant land (VL) through green infrastructure (the most common smart decline strategy) can reduce stormwater runoff and improve runoff quality, especially in legacy cities characterized by excessive industrial land uses and VL amounts. This research examines the long-term impacts of smart decline on both stormwater amounts and pollutants loads through integrating land use prediction models with green infrastructure performance models. Using the City… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…Using a case study with different scenarios of green infrastructure, the group reported significant reductions in storm water runoff and pollutants compared with the baseline [ 122 ]. Similarly, using historical flood data and changes in green infrastructure over time, they were able to identify an optimal strategy involving protecting larger green spaces near flood prone areas to reduce the costs associated with flood damage [ 123 ].…”
Section: Understanding Effects and Protecting Healthmentioning
confidence: 99%
“…Using a case study with different scenarios of green infrastructure, the group reported significant reductions in storm water runoff and pollutants compared with the baseline [ 122 ]. Similarly, using historical flood data and changes in green infrastructure over time, they were able to identify an optimal strategy involving protecting larger green spaces near flood prone areas to reduce the costs associated with flood damage [ 123 ].…”
Section: Understanding Effects and Protecting Healthmentioning
confidence: 99%
“…Cities create their own climate, such as the urban heat island, and have localized pollution, adding environmental stress to the atmosphere, exacerbating the warming effect seen on a regional scale. With the increasing intensity and frequency of urban flooding incidents caused by hurricanes or storms, legacy cities with many brownfields, vacant lands, and outdated infrastructure will also need to deal with growing risks of flood-related contamination (Nair et al, 2019;Zhu & Newman, 2021). The urban disaster caused by an increasing number of extreme weather episodes is an international challenge and a significant source of fatalities, property loss, social disruption and inequality.…”
mentioning
confidence: 99%
“…p, 526.) (32) Some studies have demonstrated that consolidation of future vacant areas functions by modeling urban forecasting and the use of green infrastructure by re-greening vacant plots can lead to Reduced urban pollution, address natural disasters in places of floods, and also in old cities that contain large industrial land uses by incorporating land use (Zhu & Newman (2021)…”
mentioning
confidence: 99%